Peningkatan Kemampuan Pemahaman Matematika Siswa dengan Quided Discovery Learning Menggunakan PhET Simulation - Adriantho Benny Pasaribu (Jurnal Didaktika Pendidikan Dasar, 2022)
This research aims to know the improvement of students comprehension skills who are taught using the quided discovery learning approach with PhET simulaion media, the ordinary learning. Next, find out whether there is a significant interaction between the learning approach and the level of mathematical ability to increase the ability to understand mathematics and see how the character strengthening is seen in the experimental class. The research method used is a quasi-experimental with a pretest-posttest control group design. The results of data analysis showed that the increase in students understanding abilities taught by using the quided discovery learning approach with the help of PhET simulation media was not higher than the quided discovery learning approach without PhET Simulation. However, the increase in students understanding ability is taught using a quided discovery learning approach with the help of PhET simulation media or without PhET, which is higher than the usual learning approach. Furthermore, there is a significant interaction between the learning approach and the level of mathematical ability to increase the ability to understand mathematics with a value of Fcount = 5.671>Ftable = F(4.774) = 2.37 or sig = 0.000 <0.05. Finally, there is character strengthening in the experimental class.